Fluid Structure Interaction (FSI): study of multiphase flow at T-junction - Mohamad Zaini, Siti Mayamin (2018)
In oil and gas industry, multiphase flow is a common phenomenon of the flow happened during the production phase. Multiphase flow is considered as a complex flow regime and need extra analysis tool to separate the fluid. The example of multiphase flow are gas-liquid flow, liquid-solid flow and solid-gas flow. Hence, pipeline is the most important equipment in industrial application to provide a good channel for the transportation of the multiphase flow. T-junction is the one of the important component of the pipeline system. The simulation of the multiphase flow when entering the T-junction is analyse by using Computational Fluid Dynamic (CFD). Eulerian model is utilized using software ANSYS FLUENT Workbench 15.0. The paper presents the modelling of the multiphase flow and the deformation of the structure when the fluid is impacting the T-junction. The Fluid Structure Interaction (FSI) of the multiphase flow on the T-junction that causing to the erosion is investigated.